Innovative Microemulsion Loaded with Unusual Dimeric Flavonoids from Fridericia platyphylla (Cham.) L.G. Lohmann Roots - do Nascimento, Jessyane Rodrigues [UNESP]; Santiago, Beatriz; Rodrigues, Matheus; Lopes, Gláucia Laís Nunes; Ferreira, Glaucio Monteiro; de Souza Nunes, Glécilla Colombelli; Gonçalves, Renato Sonchini; Carvalho, André Luis Menezes; Vilegas, Wagner [UNESP]; da Rocha, Cláudia Quintino (Springer Nature, 2023)
Fridericia platyphylla (Cham.) L.G. Lohmann is a species native to the Brazilian cerrado, with promising bioactivity. The organic fraction of the roots is rich in unusual dimeric flavonoids, reported as potential candidates for cancer treatment. The exploration of these flavonoids is very important, considering their diverse biological activities and the need for innovative therapeutic options. This work aimed to develop and characterize a microemulsion loaded with a non-polar fraction (DCM). The constituents were chosen, and the pseudo-ternary diagram was constructed to determine the region of microemulsion formation. The microemulsions blank (ME), with 3% (ME3) and 5% (ME5) of fraction DCM, were characterized in terms of droplet size, zeta potential, and polydispersity index. Both MEs showed particle sizes <100 nm; only ME3 exhibited better values for polydispersity index and zeta potential and was therefore selected for further study. The organoleptic and physicochemical characteristics were evaluated, revealing limpidity and transparency typical of these microstructures, physiologically acceptable pH, refractive index of 1.42±0.01, and density of 1.017 g/cm3±0.01. The stability tests showed good stability profiles even after exposure to extreme thermal conditions, with minimal changes in pH and the content of the incorporated fraction. The in vitro release study demonstrated that ME3 enabled the controlled release of the fraction, with a cumulative amount released over 60% within 6 h. Furthermore, fraction DCM and ME3 exhibited no toxicity in Tenebrio molitor larvae. The developed microemulsion exhibited excellent properties, so this study represents the first successful attempt to develop a formulation that incorporates the dimeric flavonoid fraction. Graphical Abstract: [Figure not available: see fulltext.]
Keywords: brachydins; dimeric flavonoids; fridericia platyphylla; microemulsion